2012
DOI: 10.1155/2012/504189
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bariatric Surgery Weight Loss on Knee Pain in Patients with Osteoarthritis of the Knee

Abstract: Studies have shown that osteoarthritis (OA) is highly associated with obesity, and individuals clinically defined as obese (BMI > 30.0 kg/m2) are four times more likely to have knee OA over the general population. The purpose of this research was to examine if isolated weight loss improved knee symptoms in patients with osteoarthritis. Adult patients (n = 24; age 18–70; BMI > 35 kg/m2) with clinical and radiographic evidence of knee OA participated in a one-year trial in which WOMAC and KOOS surveys were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 22 publications
(32 reference statements)
1
38
0
3
Order By: Relevance
“…The findings from this study reinforce shorter-term results from studies that have reported significant improvements in SF-36 bodily pain and physical function scores, 2932 WOMAC scores, 29,33,34 walking capacity (as measured by the LDCW or the 6-minute walk test), 30,31,35,36 resting heart rate, 35,36 or other measures of pain and function 1012 in the first 3 to 12 months following RYGB or LAGB. Few studies have reported on pain and function from longer-term follow-up of these procedures.…”
Section: Discussionsupporting
confidence: 84%
“…The findings from this study reinforce shorter-term results from studies that have reported significant improvements in SF-36 bodily pain and physical function scores, 2932 WOMAC scores, 29,33,34 walking capacity (as measured by the LDCW or the 6-minute walk test), 30,31,35,36 resting heart rate, 35,36 or other measures of pain and function 1012 in the first 3 to 12 months following RYGB or LAGB. Few studies have reported on pain and function from longer-term follow-up of these procedures.…”
Section: Discussionsupporting
confidence: 84%
“…27 Obesity is related with these changes by means of two interconnected pathways: increased load caused by excessive weight, and systemic effects related with chronic inflammation linked to imbalance in the release of active peptides produced by the fat tissue known as adipocytokines. 22,28,29 The assessment of knee-related symptoms using KOOS score in this study has shown impact mainly regarding pain and other symptoms compared with the mean values in non-obese individuals as reported in a systematic review by Collins et al 30 In a prospective study, Edwards et al 31 observed significant improvement in the five domains of KOOS following weight loss, while Gudbergsen et al 32 reported improvement in pain and function in daily living domains after weight loss. Thus, the results observed in our study regarding the KOOS methodology were similar to those previously observed in the literature.…”
Section: Discussionmentioning
confidence: 58%
“…The intensity of knee pain was not correlated with the amount of weight loss in one study . Improvement of WOMAC and KOOS scores were positively correlated with amount of weight loss in one study (not significant) . Recovery rates for work‐restricting knee pain was found significantly related with amount of weight loss in one study .…”
Section: Resultsmentioning
confidence: 85%
“…Ten out of 13 studies (77%) reported a significant improvement in at least one of these assessments. When taken all the different assessments together, 14 out of the 19 different assessments (73%) found a significant improvement .…”
Section: Resultsmentioning
confidence: 99%